DESKRIPSI PENERAPAN PENDEKATAN SAINTIFIK BERBANTUAN MEDIA SWISHMAX PADA SISWA SMP - Samsiya; Fury Styo Siskawati (Jurnal Penalaran dan Riset Matematika, 2024)
The purpose of the research is to describe the process of scientific approach assisted by Swishmax media in learning mathematics on the subject of cubes and blocks in eight classes of SMPN 01 Pakusari. The type of research is descriptive with a qualitative approach. The research subjects were one mathematics teacher in eight courses of SMPN 01 Pakusari and one colleague. Then for auxiliary subjects in this research were three students with high, medium, and low score categories. The data collection method used is in the form of observation, questionnaires, interviews, and documentation. The data analysis method was carried out in 5 stages, namely data transcription, data reduction, validating or triangulating data, presenting data, and drawing conclusions. The results of the research obtained were preliminary activities containing greetings, praying together, attending, conveying learning objectives and conveying the material to be studied, and doing apperception. At the core of the activity is observing, asking questions, trying to reason, and communicating the mathematical ideas learned. The closing contains reflections by inviting students to make summaries, giving homework, then inviting students to pray, and closing the lesson with greetings.